The Current State of Banking Reform - George G. Kaufman (Levy Economics Institute of Bard College, 1993)
Banking reform has always been a part of the political agenda, although policy tends to focus on the specific concerns of the public at the time of crisis; as times (and crises) change, so does the direction of public policy. The result has often been that change instituted in answer to one crisis has precipitated ensuing crises. The recent number of bank failures and resulting losses have caused public attention to once again focus on the banking system and what public policy can do to repair existing problems. In this light, Kaufman reviews the history, circumstances, and results banking reform in the 60 years since passage of the Glass-Steagall Act and speculates on the likelihood and direction of future reform.
Keywords: 330